Fabrikasi Pisau Rotor Traktor Manual Baja Karbon Menengah Ukuran 220×80×8 mm, Kapasitas 0,5 Biji/Jam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The problem in manual tractors lies in the rotor blades that are not wear-resistant and their dimensions are not up to standard. The purpose of fabrication is to obtain medium carbon steel manual tractor rotor blades measuring 220×80×8 mm. Fabrication methods include: standard blade design measuring 220 mm long, 80 mm wide, 8 mm thick, and 9 mm hole diameter, selection of used leaf spring steel type SUP9A measuring 500×90x10 mm, cutting used leaf springs, straightening used leaf springs, forging used leaf springs, drilling used leaf springs with a diameter of 9 mm, hardening at 850°C, tempering at 450°C, sharpening tractor rotary blades, finishing, product quality hardness testing. The fabrication results are in the form of a manual tractor rotary blade with dimensions of 220 × 80 × 8 mm from used SUP9A spring steel which is forged with a hardening hardness value of 55 HRC which is higher than the standard value of 50 HRC or 10% harder and the tempering results reach 45 HRC, the total production cost is IDR 80,000/unit and the processing duration is 130 minutes/unit which implies that the rotor blade is wear-resistant and has met the dimensional standards.